2010
DOI: 10.1097/mpg.0b013e3181cd2653
|View full text |Cite
|
Sign up to set email alerts
|

Cow's‐Milk–free Diet as a Therapeutic Option in Childhood Chronic Constipation

Abstract: A clear association between CM consumption and constipation has been found in more than one third of children. However, analytical parameters do not demonstrate an immunoglobulin E-mediated immunologic mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
1
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 21 publications
0
41
1
9
Order By: Relevance
“…Furthermore, it was recently shown that CM-sensitized mice without previous exposure to SP elicited hypersensitivity signs immediately after the oral administration of SP, suggesting that immunochemical cross-reactivity might be clinically relevant [27]. Consistent with these indications, Irastorza et al [14] did not allow their patients to ingest soy. However, in 2009, Australian GL on the diet management of CMA [28] suggested soy milk as the first choice for children older than 6 months without failure to thrive, in order to resolve constipation (and, more generally, gastrointestinal syndromes such as gastroesophageal reflux disease, allergic eosinophilic gastroenteritis, food protein-induced enteropathy, and colics).…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Furthermore, it was recently shown that CM-sensitized mice without previous exposure to SP elicited hypersensitivity signs immediately after the oral administration of SP, suggesting that immunochemical cross-reactivity might be clinically relevant [27]. Consistent with these indications, Irastorza et al [14] did not allow their patients to ingest soy. However, in 2009, Australian GL on the diet management of CMA [28] suggested soy milk as the first choice for children older than 6 months without failure to thrive, in order to resolve constipation (and, more generally, gastrointestinal syndromes such as gastroesophageal reflux disease, allergic eosinophilic gastroenteritis, food protein-induced enteropathy, and colics).…”
Section: Discussionmentioning
confidence: 50%
“…The terms ‘constipation' and ‘milk hypersensitivity' were searched also as Medical Subject Headings (MeSH terms). We identified 110 studies and 10 [7,8,9,10,11,12,13,14,15,16] were eligible for our review. Their most relevant features are showed in table 1.…”
Section: Research Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Irastorza et al (33) found in an open-label crossover study that 27 (39%) patients responded to a three-week CMP-elimination diet. Afterwards, all of them experienced constipation within two to five days during the three-week cow's milk challenge.…”
Section: Food Allergy and Fcmentioning
confidence: 99%
“…Research has provided conflicting results [77][78] . Therefore, testing for CMP allergy is not recommended.…”
Section: Investigationsmentioning
confidence: 99%